2013
DOI: 10.1371/journal.pone.0073516
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor Autoantibodies Correlate with Symptoms in Sydenham's Chorea

Abstract: BackgroundSydenham chorea (SC), a neuropsychiatric sequela of group-A streptococcal infection, is associated with basal ganglia autoantibodies. Although autoantibodies have been proposed in neuropsychiatric disorders, little evidence has been shown to link autoimmunity and clinical symptoms. We hypothesized that dopamine receptor-autoantibody interactions may be the basis of neuropsychiatric symptoms in SC.MethodsSera from 22 children with SC (age 10.7±4.5 years) and 22 age-matched controls were studied. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 26 publications
3
96
1
1
Order By: Relevance
“…Extracellular N-terminus hemagglutinin (HA)-tagged human D2R (www.cdna.org) and the (untagged) human NR1 subunit of NMDAR (kind gift from Professor A. Vincent, FRCPath, Nuffield Department of Clinical Neurosciences, Oxford University, United Kingdom) were subcloned into the pIRES2-eGFP vector (Clontech, Mountain View, California) as previously described (19,25,26). The bicistronic pIRES2-eGFP vector enables co-expression of distinct green fluorescent protein and receptor molecules.…”
Section: Expression Of Surface D2r and Nr1mentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular N-terminus hemagglutinin (HA)-tagged human D2R (www.cdna.org) and the (untagged) human NR1 subunit of NMDAR (kind gift from Professor A. Vincent, FRCPath, Nuffield Department of Clinical Neurosciences, Oxford University, United Kingdom) were subcloned into the pIRES2-eGFP vector (Clontech, Mountain View, California) as previously described (19,25,26). The bicistronic pIRES2-eGFP vector enables co-expression of distinct green fluorescent protein and receptor molecules.…”
Section: Expression Of Surface D2r and Nr1mentioning
confidence: 99%
“…Data analysis was performed using FlowJo software (TreeStar, Ashland, Oregon) and Excel (Microsoft, Redmond, Washington) and antibody binding was expressed as mean fluorescence intensity (MFI) as previously described (19,27,28). Specific antibody binding to D2R or NR1 was measured as the difference between the binding to HEK293 D2R1 and HEK293 NR11 cells and the binding to HEK293 D2R2 and HEK293 NR12 cells and was labeled ΔMFI.…”
Section: Immune-mediated Mechanisms In Childhood Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…with elevated antineuronal antibodies. Our previous work has supported this idea by demonstrating antistreptococcal/antineuronal antibody binding, including human monoclonal antibodies, to human neuronal cells and activation of CaMKII by sera IgG from SC and PANDAS patients (Kirvan et al 2003(Kirvan et al , 2006a(Kirvan et al ,b, 2007Brimberg et al 2012;Ben Pazi et al 2013;Cox et al 2013). We previously reported that antibody titers against neuronal antigens, lysoganglioside, and tubulin were significantly elevated in acute SC sera compared with convalescent sera.…”
Section: Figmentioning
confidence: 88%
“…Immune abnormalities have been frequently observed in PANDAS patients [46][47][48], including findings analogous to those seen in SC, such as evidence of GAS-mediated anti-neuronal autoantibodies, dopamine receptor autoantibodies, and basal ganglia pathology [49,50]. Three putative antibodies that have been implicated in SC, including N-acetyl-beta-D-glucosamine (a streptococcal group-A carbohydrate antigen), tubulin, and dopamine 2 [46][47][48].…”
Section: Autoimmune Implicationsmentioning
confidence: 99%